Assessing the challenges of public participation in Capricorn District Municipality: the case of Integrated Development Planning Process in Lepelle-Nkumpi Local Municipality - Mphahlele, Stella Letsoalelo (University of Limpopo (Turfloop Campus), 2011)
Public participation in South Africa is provided for in various legislative prescripts, not limited to the Constitution of the Republic of South Africa, 1996; White Paper on Local Government, 1998; Local Government: Municipal Structures Act, Act 117 of 1998; Local Government: Municipal Systems Act, Act 32 of 2000. Whereas all 283 municipalities in South Africa are required, as per these legislative prescripts, to conduct community participation, and whereas the same municipalities are pursuing the Integrated Development Planning Process (IDPP), community participation is not immune from problems and challenges. Pursuant to this, the research assessed public participation in the municipality under study, and found that these problems and challenges include among others, resource constraints; abuse of participatory structures by community elites and opportunists; marginalization of communities from decision-making; legitimacy of structures, through which the public participates. In addition, the following were identified: lack of creation of democratic culture of rights; lack of induction of the citizenry into democratic discourse and practice; lack of creation of mutual, reciprocal, and political tolerance; and a normative consensus as some key issues that will not auger well for a conducive public participatory environment in developmental planning processes. To be specific, the municipality under study has failed dismally in addressing certain areas of community participation in the municipality’s IDPP, such as, providing transport to members of the public to attend public participatory forums, utilization of ward committees as platforms for community participation, and ensuring representation of previously disadvantaged groups. vi Based on the critical issues raised and conclusions drawn, the study has therefore provided possible recommendations to resolve the problems and challenges of public participation in the municipality under study. Although the problems and challenges may not necessarily be generalized to other municipalities, the recommendations proffered, can also be populated to other municipalities, to add value in enhancing respective public participation, which is believed to consequently influence positively on service delivery
Thesis (MPA)--University of Limpopo (Turfloop Campus), 2011
Keywords: Municipalities; Public participation; 351.68; Public administration - South Africa - Limpopo.; Political participation - South Africa - Limpopo